Synthesis and In Vitro Antimicrobial, Anthelmintic and Insecticidal Activities Study of 4(4'-Bromophenyl)-6-substituted-aryl-1-acetyl pyrimidine-2-thiols - Rita Bamnela; S. P. Shrivastava (E-Journal of Chemistry)
A new series of 4(4'-bromophenyl)-6-substituted aryl-1-acetyl pyrimidine-2-thiol derivatives were synthesized by heating chalcones with thiourea, in the presence of ethanolic potassium hydroxide, followed by treatment with acetyl chloride. The structure of the compounds was characterized by IR and H1 NMR spectral study and elemental analysis. The compounds were screened for their antimicrobial, anthelmintic and insecticidal activities. All the compounds exhibited significant to moderate biological activities.